Respiratory Distress Secondary to Esophageal Foreign Body. A Case Report - Jacob Urkin; Yair Bar-David (The Scientific World Journal)
The ingestion or aspiration of a foreign body is a common, but preventable occurrence in childhood. Primary healthcare personnel should alert parents to the risk of swallowing a foreign object, the signs and the need for immediate medical attention. It should be emphasized that protecting children from access to objects that can be swallowed or aspirated is the best preventive measure. A case of an eight year old child, who had swallowed a marble ball is presented and the symptoms and intervention discussed. Medical staff should be aware of the symptomatic variation in ingested foreign body presentation and the importance of rapid diagnosis and management.